1984
DOI: 10.1021/ma00135a019
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-13 NMR study of curing in furfuryl alcohol resins

Abstract: A13C CP/MAS NMR study of furfuryl alcohol resins is reported. A conformational rigidity is found for uncured or less cured resins. The contents of methylol groups and dimethylene ether linkages are found to be very small. It is postulated that cross-linking involves the breaking of methylene bridges in the curing process. Further confirmation is given that the major cross-linking processes that occur during curing involve linkages with bridging CH2 groups, rather than substitution at the 3-and 4-positions of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(62 citation statements)
references
References 1 publication
2
59
1
Order By: Relevance
“…Various reactions have been proposed for the crosslinking of fufuryl alcohol resins [24][25][26], including reaction of carbocationic chain ends with preformed methylene links; see Scheme 4, Reaction (4). However, Choura et al found no evidence for Reaction (4) when tested with model compounds.…”
Section: Physical Appearances Of Cured Resins and Resin Blendsmentioning
confidence: 99%
“…Various reactions have been proposed for the crosslinking of fufuryl alcohol resins [24][25][26], including reaction of carbocationic chain ends with preformed methylene links; see Scheme 4, Reaction (4). However, Choura et al found no evidence for Reaction (4) when tested with model compounds.…”
Section: Physical Appearances Of Cured Resins and Resin Blendsmentioning
confidence: 99%
“…FA is often obtained from agricultural waste such as sugar cane, corn cobs, sunflower or birch chips (Maciel et al 1982;Chuang et al 1984;González et al 1992González et al , 2002Lande et al 2008). According to Lande et al (2004), furfurylation of wood provides protection against bio-degradation (fungi, bacteria and marine borers) without reliance on biocidal treatments.…”
Section: Introductionmentioning
confidence: 99%
“…According to the reported polymerized structures, the humin structure contains methylene linkage furan rings [26,27], dimethylene ether linkage [20], γ-diketone [28], conjugated double bond sequence [3,23,29], and branched species [30,31]. Even though proposed structures were contradictory in some respects, the observed sample's color, which is dark gray or black, and viscous character were commonly agreed.…”
Section: Introductionmentioning
confidence: 99%